2003
DOI: 10.1073/pnas.1332550100
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic, yet structured: The cell membrane three decades after the Singer–Nicolson model

Abstract: The fluid mosaic membrane model proved to be a very useful hypothesis in explaining many, but certainly not all, phenomena taking place in biological membranes. New experimental data show that the compartmentalization of membrane components can be as important for effective signal transduction as is the fluidity of the membrane. In this work, we pay tribute to the Singer-Nicolson model, which is near its 30th anniversary, honoring its basic features, ''mosaicism'' and ''diffusion,'' which predict the intersper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
392
0
12

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 473 publications
(408 citation statements)
references
References 112 publications
4
392
0
12
Order By: Relevance
“…A recent study investigating T2 relaxation time the in vivo brain effects of omega-3 fatty acids using T2 relaxation time in patients with bipolar affective disorder supports preclinical findings that omega-3 fatty acids modulate membrane integrity (Hirashima et al, 2004), thereby potentially altering signal transduction and receptor binding (Vereb et al, 2003). One way to further investigate the potential in vivo brain effects of omega-3 fatty acids is proton magnetic resonance spectroscopy (1H-MRS), which can estimate regional concentrations of various brain metabolites.…”
Section: Introductionmentioning
confidence: 72%
“…A recent study investigating T2 relaxation time the in vivo brain effects of omega-3 fatty acids using T2 relaxation time in patients with bipolar affective disorder supports preclinical findings that omega-3 fatty acids modulate membrane integrity (Hirashima et al, 2004), thereby potentially altering signal transduction and receptor binding (Vereb et al, 2003). One way to further investigate the potential in vivo brain effects of omega-3 fatty acids is proton magnetic resonance spectroscopy (1H-MRS), which can estimate regional concentrations of various brain metabolites.…”
Section: Introductionmentioning
confidence: 72%
“…It is now widely accepted that biological membranes are highly heterogeneous environments where the translational diVusion of proteins is restricted by various mechanisms (Vereb et al 2003). A good example is the clustering of molecules in membranes by mechanisms that may involve lipid-lipid, protein-protein and protein-lipid interactions.…”
Section: Signaling Via Protein Clusters In the Plasma Membranementioning
confidence: 99%
“…A good example is the clustering of molecules in membranes by mechanisms that may involve lipid-lipid, protein-protein and protein-lipid interactions. The best know examples of such a phenomenon are lipid rafts that are deWned as small cholesterol-dependent domains in membranes in which certain proteins may aggregate (Lai 2003;Simons and Toomre 2000;Vereb et al 2003). It has been suggested that such domains may play a crucial role in signal transduction by sorting the signaling molecules and modifying their output properties by increasing their local concentrations (Lai 2003;Simons and Toomre 2000;Vereb et al 2003).…”
Section: Signaling Via Protein Clusters In the Plasma Membranementioning
confidence: 99%
See 1 more Smart Citation
“…The most apparent manifestation of the FRET process is the decrease of donor fluorescence in the presence of an acceptor in close vicinity (1-10 nm), which is accompanied by an increase of fluorescence of the acceptor (if the acceptor is a fluorescent molecule). The FRET phenomenon has been adapted for microscopy (3)(4)(5)(6) and flow cytometry (7)(8)(9) and several biological structures have been successfully investigated: receptors involved in immune response (10)(11)(12), growth factor receptors on tumor cells (13)(14)(15), determination of protein conformation (16,17), and lipid microdomain structures (9,18,19). Several reviews are also available for biomedical and clinical applications of FRET (8,18,(20)(21)(22)(23)(24).…”
mentioning
confidence: 99%